2021
DOI: 10.1364/boe.426218
|View full text |Cite
|
Sign up to set email alerts
|

Full circumferential morphological analysis of Schlemm’s canal in human eyes using megahertz swept source OCT

Abstract: We performed full circumferential imaging of the Schlemm’s canal (SC) of two human eyes using a Fourier domain mode-lock laser (FDML) based 1.66-MHz SS-OCT prototype at 1060 nm. Eight volumes with overlapping margins were acquired around the limbal area with customized raster scanning patterns designed to fully cover the SC while minimizing motion artifacts. The SC was segmented from the volumes using a semi-automated active contour segmentation algorithm, whose mean dice similarity coefficient was 0.76 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…To test the 3D imaging capability we showed a 2.5-mm scanning length circumferentially. The latest published techniques for 360° imaging of the SC employed the combination of multiple volumetric scanning 47 , 48 , 53 , which might cause discontinuity between volume scans. A larger field of view could be a solution but the resolution is limited and the direction of OCT beams is not optimal for the angle imaging.…”
Section: Discussionmentioning
confidence: 99%
“…To test the 3D imaging capability we showed a 2.5-mm scanning length circumferentially. The latest published techniques for 360° imaging of the SC employed the combination of multiple volumetric scanning 47 , 48 , 53 , which might cause discontinuity between volume scans. A larger field of view could be a solution but the resolution is limited and the direction of OCT beams is not optimal for the angle imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (Huang et al, 2017) demonstrated the ability to perform a 360 °threedimensional reconstruction of SC in one healthy volunteer eye using a commercial SD-OCT instrument that included an active eye tracker to compensate for motion artifacts. Meanwhile, Yao et al (Yao et al, 2021) utilized SS-OCT to perform complete circumferential imaging of SC in two healthy human eyes. They reconstructed three-dimensional renderings of SC by stitching the segmented SCs from the volumetric datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, repeated serial measurements were performed to reduce random errors and confirm our observations. Thirdly, the AS-OCTA does not directly image the aqueous outflow tracts such as the Schlemm's canal and collector channels (49).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, repeated serial measurements were performed to reduce random errors and confirm our observations. Thirdly, the AS-OCTA does not directly image the aqueous outflow tracts such as the Schlemm's canal and collector channels ( 49 ). Ideally we should perform aqueous angiography to assess the actual flow through the collector channels—thus the Hydrus implant may not increase the flow in the collector channels.…”
Section: Discussionmentioning
confidence: 99%